Numerical investigations and capacity prediction of G-FRP rods glued into timber. (15th October 2018) - Grunwald, Cordula; Kaufmann, Marvin; Alter, Benjamin; Vallée, Till; Tannert, Thomas
Abstract: Glued-in-rods (GiR) represent a class of joints being used in timber engineering that are mostly used to transfer axial loads in structural members with Glass Fibre Reinforced Polymers (G-FRP) increasingly being considered as rod material in substitution for the usually considered metallic rods. The primary objective of the research presented herein was to apply a probabilistic capacity prediction method to timber joints with G-FRP GiR. Necessary secondary objectives were to mechanically characterise the involved components (adhesive, rods, and timber) and to numerically investigate the stress state inside the tested joints. The methodology shall be applied to a recently reported in literature Zhu et al. (2017) that was specific in two ways: firstly, G-FRP rods were bonded into both ends of the timber block with both ends being tested to failure—a deviation from common practice; and secondly, as opposed to most previous studies exhibiting stiff adhesives, a ductile Polyurethane with markedly non-linear behaviour was used. All material characterisation was performed with methods that can be reproduced by any standard laboratory equipment, to provide parameters for the subsequent numerical analyses. Based thereupon, a probabilistic method was used and provided reasonably accurate predictions of the joint capacities of 25 different geometrical GiR configurations. The probabilistic method was extended for realistic estimations of the experimental capacity scattering in form of upper and lower percentiles.